MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL KOOPERATIF TIPE STAD PADA MATA PELAJARAN PPKn DI SMP NEGERI 20 PONTIANAK - Sausan, Nida; Okianna, Okianna; Purnama, Shilmy; Sulistyarini, Sulistyarini; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to improve students' learning outcomes using the STAD cooperative learning model in Civic Education. The research method employed is theClassroom Action Research with a descriptive form. The subjects are eighth-grade students from SMP Negeri 20 Pontianak, with 32 students as samples. Data collection techniques include observation, tests, and documentation. Data instruments used are teacher activity observation sheets, student activity observation sheets, and pretest/posttest sheets for learning outcomes. The research consists of two cycles, each comprising 2 sessions. Teacher activity results were 71.73% in Cycle I and 82.5% in Cycle II. Student activity results were 42.82% in Cycle I and 63.56% in Cycle II. Students' learning outcomes improved by 46% from Cycle I to Cycle II. The average learning outcome in Cycle I was 70.94%, achieving a mastery level of 46.88% (15 students passed). In Cycle II, the average learning outcome reached 79.38% with a mastery level of 68.75% (22 students passed). In conclusion, the implementation of the STAD cooperative learning model in Civic Education improves the learning outcomes of eighth-grade students at SMP Negeri 20 Pontianak